New marker for the detection of pre-retinopathy in patients with type 1 diabetes mellitus: systemic immuno-inflammation index - Hazan Gül Kahraman; Yusuf Ziya Güven; Fahrettin Akay; Yusuf Üzüm; Murat Aysin (BMC Ophthalmology)
Abstract Purpose This study aimed to investigate the relationships among urine parameters, systemic inflammation and retinal microvascular changes in patients with type 1 diabetes mellitus (T1DM) without clinical signs of diabetic retinopathy (DR), via optical coherence tomography angiography (OCTA) and the systemic immune-inflammation index (SII). Methods A total of 64 participants, including 33 patients with T1DM and 31 healthy controls matched by age and sex, were examined. All the subjects underwent detailed eye assessments and OCTA imaging. Retinal and choroidal parameters were measured along with systemic markers such as C-reactive protein (CRP), Erythrocyte Sedimentation Rate (ESR), haemoglobin-A1C (HbA1c), spot urine tests and the SII. Relationships between systemic inflammation, renal and metabolic parameters, and ocular measurements were analyzed. Results The T1DM group had significantly higher SII values (381.78 ± 57.30 vs. 284.86 ± 67.88, p < 0.001), HbA1c values (8.21 ± 1.80 vs. 5.15 ± 0.32, p < 0.001), spot microalbumin levels (13.50 ± 26.56 vs. 0.69 ± 0.57, p = 0.009), and albumin/creatinine ratios (0.13 ± 0.31 vs. 0.01 ± 0.01, p = 0.031). No significant differences in macular thickness, vascular density (VD), or foveal avascular zone (FAZ) area were detected between the groups. However, the mean retinal nerve fiber layer (RNFL) thickness and perifoveal ganglion cell complex (GCC) thickness were significantly lower in the diabetic group (p < 0.05). The SII was strongly positively correlated with choroidal thickness (r = 0.686, p < 0.001) and negatively correlated with parafoveal GCC thickness (r=-0.357, p = 0.041). HbA1c was negatively correlated with mean VD (r=-0.261, p = 0.037). No significant correlation was found between the SII and the FAZ or VD. Significant correlations were found between the mean vascular density and both the spot creatinine level (r = -0.527, p = 0.002) and the spot microalbumin level (r = -0.355, p = 0.043). Conclusion This study highlights the potential of the SII as a biomarker for detecting early subclinical retinal and choroidal changes in T1DM patients before the onset of retinopathy. The observed correlations among spot urine tests, the SII and OCTA parameters support the role of systemic inflammation in the early microvascular alterations associated with diabetes. These findings may contribute to early diagnosis and novel preventive strategies in DR. However, given the limited sample size, these findings should be interpreted with caution. Larger, well-stratified prospective studies are warranted to validate these preliminary observations.